LAW ENFORCEMENT EFFECTS ON SOCIAL DISCIPLINE AND COMMUNITY SOCIAL INTEGRATION IN GARUT DISTRICT - Uus Sunandar; Abdal (Bajang Institute, 2021)
This research background was the less optimum of law enforcement that has caused the social discipline and social integration weakness in Garut regency. Based on it, core problem of this reseacrh was identifying as : “has the law enforcement affected the social discipline and social integration in Garut regency?”.